Coplanar Waveguide Fed Multimode Resonant Switchable Antenna - Dr. Praveen Kumar Kancherla, B.Amulya, B.Venkateshwar Rao (International Journal of Advanced Science and Technology, 2020)
In current article active coplanar waveguide feed reconfigurable multiband antenna design and its operational characteristics are presented. The designed antenna covers S-band, Wi-MAX C-Band, X-band applications. A detail study was performed to characterize the switching operation by considering the wire bound effects. The circular ring is loading with (TSIR) T-shaped stepped impedance resonator and (PSLR) parallel stub loaded resonator. The proposed structure is resonating at 3.26GHz, 4.16GHz, 8.04GHz and 8.9GHz frequencies. Proposed structure exhibiting maximum gain of 5.94 dB at 8.04 GHz. The proposed antenna shows good impedance characteristics, low profile and compact size, which is suitable for wireless communication applications. Keywords: TSIR, PSLR.